Exploring NCLEX Failures and Standardized Assessments. Issue 3 (May 2019) - Emory, Jan
Abstract : Background: Nurse educators seek valid and reliable tools to assist in early identification and intervention for students at-risk of NCLEX-RN failure. Purpose: The purpose of this cross-sectional study was to use principal component analysis to explore relationships within standardized assessment (SA) scores from a sample of students who failed the NCLEX-RN on the first attempt. Methods: Standardized assessment scores were collected from prelicensure programs between 2009 and 2016 (n = 296). Mixed modeling sought to reveal SA scores that represented redundancy or duplication. Results: The principal component analysis found 2 distinct components emerging from the 8 SAs included in the study, signifying duplication in the content assessed. Within these 2 components, maternal newborn and pharmacology had the strongest correlations among the SA scores. Conclusions: Discovering those SAs that assess similar content and have the strongest correlations can provide additional information for decision making when implementing these tests throughout the nursing curriculum. Abstract : Supplemental digital content is available in the text.